The Influence of Digital Literacy on the Learning Readiness of Midwifery Students in the Technology Era - Suciana, Ewin; Ladjamuddin, Siti Madinah; Siswosuharjo, Partono (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2026)
Digital transformation in midwifery education requires students to possess adequate digital literacy to effectively engage in technology-based learning processes. This study aims to develop and evaluate a digital literacy learning product and to analyze the impact of digital literacy on the learning readiness of midwifery students in the technological era. The study employs a Research and Development (R&D) approach comprising stages of needs analysis, product design, development, expert validation, limited trials, and effectiveness testing. The research subjects consisted of 100 midwifery students whose digital literacy and learning readiness were measured before and after using the product. Data were collected using digital literacy and learning readiness instruments that had undergone validity and reliability testing. Analysis was conducted using descriptive statistics, paired t-tests, Pearson correlation, and multiple linear regression. The results indicate that the developed learning product was rated as highly feasible by experts. Scores for digital literacy and learning readiness increased following the intervention. Bivariate analysis revealed a positive and significant relationship between digital literacy and learning readiness, while multivariate analysis showed that specific dimensions of digital literacy collectively contributed to students' learning readiness. These findings suggest that the systematic development of digital literacy can serve as a crucial strategy to enhance midwifery students' readiness for increasingly digitized learning and healthcare practice.